If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-3x + 1) + -4x = 5 + 2x Reorder the terms: 5(1 + -3x) + -4x = 5 + 2x (1 * 5 + -3x * 5) + -4x = 5 + 2x (5 + -15x) + -4x = 5 + 2x Combine like terms: -15x + -4x = -19x 5 + -19x = 5 + 2x Add '-5' to each side of the equation. 5 + -5 + -19x = 5 + -5 + 2x Combine like terms: 5 + -5 = 0 0 + -19x = 5 + -5 + 2x -19x = 5 + -5 + 2x Combine like terms: 5 + -5 = 0 -19x = 0 + 2x -19x = 2x Solving -19x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -19x + -2x = 2x + -2x Combine like terms: -19x + -2x = -21x -21x = 2x + -2x Combine like terms: 2x + -2x = 0 -21x = 0 Divide each side by '-21'. x = 0 Simplifying x = 0
| 10z+1/2=9/7+6z/7+10z/3 | | 6+6j-4=4+4j | | 2/3(x-18)= | | 105-170+132=165 | | 38+28.2837x=55 | | x-1.3=12 | | 3(m+2)=33 | | -6+3x=7x+2 | | 10/8+7/8-2/5=8x/4+2/4 | | y-5=2x-6 | | 80+45=260 | | 2/2+6=7-z/2 | | y-4=3x-3 | | m-4.8=7.4 | | w-1137=-2222 | | 2/3x+x=120 | | 4x^2=12x+91 | | 2+1/7x=9 | | -3/4-10z/7=11/5-5z/4 | | -88/11=t | | 9-x=4x+6(x-3) | | 5(8+6x)=-2x-12 | | 0.77=x | | 70-21x=75-20x | | -3-4x/2-4/2=-5x/4+7/4 | | 6(x-6)+8=8x-10 | | w-3.7=4.63 | | y=3x-3+4 | | 10x-7x+29=25+(19x-14) | | -3-4x/2-4/2=5x/4+7/4 | | 5w+7=2w-2 | | 36x+32=572 |